Męczeństwo jako paradoksalne świadectwo życia w aktach i pasjach męczenników - Kozłowski, Jan M. (Vox Patrum, 2006)
In ancient Christian literature (including the Acts of the Christian Martyrs), one can encounter many passages showing that the “eternal life” is not exactly the other life in the “world to come”, but a reality in which the Christian already participates during worldly existence.